Factors influencing general practitioners' knowledge of asthma management in primary health facilities in Medan City - Vinda Sari Ermiza Nasution; Amira Permatasari Tarigan; Andika Pradana; Rina Amelia (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Asthma is a chronic respiratory disease caused by inflammation, making the airways hypersensitive to triggers and leading to recurrent symptoms. Adequate knowledge of asthma management among general practitioners is essential to improve patient care, reduce disease severity, and prevent mortality. This study aimed to identify factors influencing general practitioners’ knowledge of asthma management in primary health facilities in Medan City. A cross-sectional study was conducted involving 90 general practitioners selected through consecutive sampling. Data collected included respondent characteristics such as age, length of service, number of asthma patients treated monthly, source of knowledge, history of asthma management training, and level of knowledge. A validated and reliable questionnaire was used (Guttman scale r = 0.489; Cronbach’s alpha = 0.93). Statistical analysis using SPSS included chi-square and Fisher’s exact tests to assess relationships between variables. Results showed that most general practitioners had enough knowledge (54.4%) about asthma management. Significant associations were found between age (p = 0.034) and source of knowledge (p = 0.048) with the level of knowledge. Other variables showed no significant relationship. In conclusion, age and source of knowledge significantly influence general practitioners' knowledge of asthma management in primary health facilities, highlighting the need for targeted educational interventions.